The moral status of invasive animal research - Rollin, Bernard E. (Henry Stewart Talks, 2015)
Societal context of invasive animal research, Legislation of animal testing, The scientific community's attitude towards the ethics of animals research, Three layers of ethical concern regarding animal research, Animal teloi